The Hieroglyphic Luwian -si Again - Oshiro, Terumasa (Lingua Posnaniensis, 2010)
We recognize three attestations of the element -si attached to a verbal ending in KARKAMIŠ A11b, A12 and ALEPO 2. The author has already regarded this -si as another reflexive element comparable to the reflexive -ti. Furthermore, we can also point out four more attestations of a similar element -si in the inscriptions recently discovered at TELL AHMAR 6: huhasata-si "he himself ran" (vii and xix) and at ÇINEKÖY: iziya-si "they themselves made" (vi and vii). It should be noted that the element -si in ÇINEKÖY is attached directly to an irregularly omitted verbal form iziya of *iziyanta "they made".